DAMPAK PERTUMBUHAN NILAI TUKAR RIIL TERHADAP PERTUMBUHAN NERACA PERDAGANGAN INDONESIA (SUATU APLIKASI MODEL VECTOR AUTOREGRESSIVE, VAR) - Zuhroh, Idah; Kaluge, David (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2007)
This study aimed to test the impact of the growth of real exchange rate towards thegrowth of Indonesian trade balance by using Vector Autoregressive (VAR) Model.By using quarterly data from 1983.1 to 2005.4 periods, the result obtained is inaccordance with other countries which response positively the depreciation ofexchange rate in long term or follow the phenomenon of J-curve. However, the rate ofgrowth is still weak in explaining the growth of trade balance because the model isonly significant estimates at á and based on the decomposition of variation of growthsurprises of real exchange rate is only 2.7% in average which explained the variationof trade balance growth.Keywords: Jcurve, real exchange rate, trade balance Vector Autoregressive.